CHARACTERISTICS OF KNEE JOINT’S ULTRASOUND AND MAGNETIC RESONANCE IMAGING ON PATENTS WITH PRIMARY KNEE OSTEOARTHRITIS (Vietnam Journal of Community Medicine, 2021)
Objectives: Describing the characteristics of ultrasound and magnetic resonance imaging of knee joints in patients with primary knee osteoarthritis.Subjects and methods: Prospective, descriptive, cross-sectional study on patients diagnosed with primary knee osteoarthritis who were examined as an outpatient or inpatient at 108 Military CentralHospital.Results: Ultrasound features: 100% articular cartilage damage, 87.8% bone spurs, 73.0% effusion, 9.3% popliteal cocoon, 3.4% synovial thickening. Degree of cartilage damage according toSaarakkala: grade 1: 2.1%, grade 2A: 63.7%, grade 2B: 29.1%, grade 3: 5.1%. Magnetic resonance characteristics: 100% articular cartilage damage, 96.3% bone spurs, 90.6% effusion, 84.1% bonemarrow edema, 69.2% bone cocoon, 61.7% meniscus tear, popliteal cocoon 11.3%. osteoarthritis lesions were more common in the medial femoral and tibial joints than in the lateral tibial and patellar joints.Conclusion: Cartilage damage, bone spurs, and effusion were common lessions on ultrasound and magnetic resonance imaging on patients with knee osteoarthritis.
Keywords: Ultrasound, magnetic resonance, primary knee osteoarthritis